1998
DOI: 10.1002/(sici)1097-0304(199806)44:2<147::aid-ccd5>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve in the use of the radial artery as vascular access in the performance of percutaneous transluminal coronary angioplasty

Abstract: Radial artery access for coronary artery angioplasty is a cost‐effective alternative to other vascular entry sites. The initial series of patients using the radial artery site for an operator without experience in using arm access for coronary artery angioplasty was evaluated. Clinical success was achieved via the radial artery in 87% of 32 lesions and 84% of 27 patients. The major feature limiting success via the arm was radial/brachial artery spasm, which occurred in 30% of cases (clinical success: 50% with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(39 citation statements)
references
References 13 publications
1
33
1
4
Order By: Relevance
“…However, concerns have been raised about prolonged procedure time and increased radiation exposure to the operators by using radial route of access (4)(5)(6). Although, some studies have shown that with increasing operator experience radiation exposure can be minimized with transradial approach (TRA) and hence majority of radial operators assume that special radiation exposure precautions are unnecessary (7,8). On the contrary, few other studies demonstrated increased fluoroscopy time and radiation exposure with radial access and advocated special radiation protection methods to reduce operator radiation exposure (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns have been raised about prolonged procedure time and increased radiation exposure to the operators by using radial route of access (4)(5)(6). Although, some studies have shown that with increasing operator experience radiation exposure can be minimized with transradial approach (TRA) and hence majority of radial operators assume that special radiation exposure precautions are unnecessary (7,8). On the contrary, few other studies demonstrated increased fluoroscopy time and radiation exposure with radial access and advocated special radiation protection methods to reduce operator radiation exposure (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…17 Many studies done in the past have used different spasmolytic regimens. 5,8,9,16 In one of the similar studies publish by Kiemeneij et al 14 which was a prospective study proved that intra-arterial administration of 5 mg of verapamil and 200 mcg of nitroglycerin reduced the occurrence and severity of radial artery spasm. The data showed the evidence of benefit of verapamil in the prevention of spasm but concern still remains regarding the negative inotropic and chronotropic effects of verapamil.…”
Section: Discussionmentioning
confidence: 90%
“…The prevention of spasm is easy than to control when it occurs. 8 He and yang classification classifies the radial artery into type III artery graft with high propensity for spasm and also as stated above due to abundance of the alpha receptors slight cathecholamine release during pain or anxiety can induce radial spasm. 17 Many studies done in the past have used different spasmolytic regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deambulação precoce, permitida pelo acesso radial, produz maior conforto e reduz os custos da hospitalização [4][5][6] . No entanto, o acesso transradial é algumas vezes tecnicamente mais trabalhoso e delicado, demandando maior período de aprendizagem para os operadores [7][8][9] .…”
Section: Discussionunclassified